New mechanistic insights into the Claisen rearrangement of chorismate – a Unified Reaction Valley Approach study. (18th June 2019) - Freindorf, Marek; Tao, Yunwen; Sethio, Daniel; Cremer, Dieter; Kraka, Elfi
ABSTRACT: The Bacillus subtilis chorismate mutase catalysed Claisen rearrangement of chorismate to prephenate is one of the few pericyclic processes in biology, and as such provides a rare opportunity for understanding how Nature promotes such rearrangements so successfully. The major focus of this work is on (i) Exploring the hypothesis that the mechanism of the chorismate rearrangement is the same in the gas phase, in the aqueous solution and in the enzyme; (ii) Investigating current suggestions that the enzyme lowers the barrier via transition state stabilisation rather than via space confinement; and (iii) A comparison of Nature's way of catalysing the reaction with a gold(I) catalysed chorismate rearrangement. Based the Unified Reaction Valley Approach (URVA), for the first time, a detailed one-to-one comparison of the rearrangement in the gas phase, in the aqueous solution and in the enzyme is presented. URVA confirms that the actual chemical process of CO bond breaking and CC bond forming is the same for all media and unravels the unique catalytic function of the enzyme as a combination of shortening the process of positioning the enolpyruvyl side chain over the cyclohexadienyl ring by space confinement in concert with facilitating CO cleavage by enhanced charge polarisation. The transition state does not play a signifiant role for the rearrangement. In contrast, the gold catalyst changes the chemical process. The rearrangement is split into two steps by switching between Au[I]- π and Au[I]- σ complexation, thus avoiding the energy consuming CO breakage in the first step. Suggestions are made for metalloenzyme analogues combining both strategies. GRAPHICAL ABSTRACT: